Trigeminal Nerve Root Demyelination Not Seen in Six Horses Diagnosed with Trigeminal-Mediated Headshaking - Roberts, Veronica L.; Fews, Debra; McNamara, Jennifer M.; Love, Seth (Frontiers in Veterinary Science, 2017)
Abstract: Trigeminal-mediated headshaking is an idiopathic neuropathic facial pain syndrome in horses. There are clinical similarities to trigeminal neuralgia, a neuropathic facial pain syndrome in man, which is usually caused by demyelination of trigeminal sensory fibres within either the nerve root or, less commonly, the brainstem. Our hypothesis was that the neuropathological substrate of headshaking in horses is similar to that of trigeminal neuralgia in man. Trigeminal nerves, nerve roots, ganglia, infraorbital and caudal nasal nerves from horse abattoir specimens and from horses euthanased due to trigeminal-mediated headshaking were removed, fixed and processed for histological assessment by a veterinary pathologist and a neuropathologist with particular experience of trigeminal neuralgia histology. No histological differences were detected between samples from horses with headshaking and those from normal horses. These results suggest that trigeminal-mediated headshaking may have a different pathological substrate from trigeminal neuralgia in man.